Pengaruh Target Kerja Dan Pengawasan Terhadap Kinerja Karyawan Indomaret (Studi Kasus Indomaret Wilayah Medan Amplas) - Muspri Yani, Muspri Yani; Amir Makhmud Zain Nst; Yuni Andri Ekawati (Sekolah Tinggi Ilmu Manajemen Sukma, 2025)
Based on the results of primary data regression processed using SPSS 20, the multiple linear regression equation is obtained as follows: Y = 1.897 + 0.246 X1 + 0.746 X2 + e. Partially, the work target variable (X1) has a significant influence on employee performance, as evidenced by the calculated t value > t table (2.826 > 2.051). The supervision variable (X2) has a significant influence on employee performance, as evidenced by the calculated t value > t table (7.624 > 2.051). Simultaneously, the work target variable (X1) and supervision (X2) have a significant influence on employee performance. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (49.133 > 3.35). The work target variable (X1) and supervision (X2) are able to contribute influence on employee performance variables by 78.4% while the remaining 21.6% is influenced by other variables not examined in this study.